2015
DOI: 10.1002/trtr.1365
|View full text |Cite
|
Sign up to set email alerts
|

Motivation

Abstract: Thinking of motivation not as a solitary concept but as a set of componentsenables teachers to select appropriate assessments, interpret the data they provide, and plan truly motivating instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(25 reference statements)
1
19
0
8
Order By: Relevance
“…The results of this study show that students' reading amount in L2 positively predicted their reading comprehension in L2 (Mol & Bus, 2011;Schaffner et al, 2013). These substantial effects of reading amount on reading comprehension can be interpreted in the context of educational psychology in terms of practice in reading literacy.…”
Section: Summary and Interpretationmentioning
confidence: 54%
See 2 more Smart Citations
“…The results of this study show that students' reading amount in L2 positively predicted their reading comprehension in L2 (Mol & Bus, 2011;Schaffner et al, 2013). These substantial effects of reading amount on reading comprehension can be interpreted in the context of educational psychology in terms of practice in reading literacy.…”
Section: Summary and Interpretationmentioning
confidence: 54%
“…Competence in reading comprehension is influenced by multiple determinants such as reading motivation, prior knowledge/previous reading literacy, and cognitive skills (e.g., Becker, McElvany, & Kortenbruck, 2010). Additionally, various studies have pointed to students' reading amount as a relevant factor for reading literacy (see Mol & Bus, 2011, for a meta-analysis; see Schaffner et al, 2013, for a German sample of primary school students).…”
Section: Reading Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…H elping students grow as independent readers has long been an important issue among reading researchers and educators. In the past, the cognitive dimensions of reading, such as word recognition and comprehension, have dominated reading research and resulted in a range of effective approaches (Jang, Conradi, McKenna, & Jones, 2015). The affective dimensions, such as motivation and attitude, in contrast, have been largely neglected.…”
Section: Xiaocheng Wang Yuanying Jinmentioning
confidence: 99%
“…Research showed that the continuing professional development (CPD) of teachers is a requirement to ensure high quality education (Coe, Aloisi, Higgins, & Major, 2014;McArdle & Coutts, 2010;OECD, 2014;Postholm, 2012;Wei, Darling-Hammond, Andree, Richardson, & Orphanos, 2009). This is also the case when it comes to reading motivation promotion (De Naeghel et al, 2014, 2016Guthrie & Klauda, 2014;Jang, Conradi, McKenna, & Jones, 2015). Kelchtermans (2004) defines CPD as "a learning process resulting from meaningful interaction with the context (both in time and space) and eventually leading to changes in teachers' professional practice (actions) and in their thinking about that practice" (p. 220).…”
Section: Introductionmentioning
confidence: 99%